E-Government Public Relations: A Systematic Literature - Ahmad Sahal Alamsyah Jajuli; Salahudin Salahudin; Muhammad Firdaus (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2024)
This research aims to identify and describe the implementation of Government Public Relations based on digital technology or commonly referred to as E-Government Public Relations in a government system and can be used as study material. The research method used is qualitative research with a descriptive approach and a case study research model in conducting research regarding the implementation of E-Government Public Relations. What was applied in this research was a systematic literature review using 500 scientific articles sourced from the Scopus database. Review articles using the Vosviewer application. The research results reveal that E-Government Public Relations has a significant function and role in the activities and communication activities of government institutions which aim to improve services, meet public information needs and build and create a good communication climate between institutions and their stakeholders through various means. communication media platforms. Public Relations as a management function which aims to build, maintain and create quality communication, understanding and cooperation between an organization and its public, he also added that PR involves problem management or issue management, because PR is also responsible for assisting organizational management. The limitation of this research is that the articles used only come from the Scopus database so that the research findings cannot comprehensively describe the issue of digital transformation in e-government public relations. Future research needs to use scientific articles sourced from other reputable international databases, such as Web of Science and Dimensionds Scholars.